IMPLEMENTATION OF THE COMMUNITY SERVICE PROGRAM IN IMPROVING STUDENTS' ENGLISH LITERACY AND NUMERACY SKILLS AT SDN 091409 SARIMATONDANG - Lastri Wahyuni Manurung; Galina Sitinjak; Anita Theresia Br Saragi; Hesty Malinda Manalu; Lusi Manurung; Rachel Br Sidabutar; Yuniarta Br Hutasoit (Abdimas Galuh, 2023)
The Community Service Program (PKM) aims to improve students' English literacy and numeracy skills and develop a culture of English literacy and numeracy within SD Negeri 091409 Sarimatondang. This form of community service activity is carried out in 3 states of activity: Literacy and Numeracy Learning Activities in English "English Day," Additional Lesson Hours Activities, and Repair of library archives. This activity begins February 6 – 25, 2023. The subjects of this community service are all grade 1 – 6 students at SD Negeri 091409 Sarimatondang. The method of implementing this activity consists of several stages: Preparation, Implementation, and Evaluation. The results of community service obtained are the success of increasing students' literacy, and numeracy abilities, and students have been able to implement it as a new culture in the school environment.